A Highly Efficient Molecular Cloning Platform that Utilises a Small Bacterial Toxin Gene. Issue 6 (19th March 2013) - Mok, Wendy W. K.; Li, Yingfu
Abstract Molecular cloning technologies that have emerged in recent years are more efficient and simpler to use than traditional strategies, but many have the disadvantages of requiring multiple steps and expensive proprietary enzymes. We have engineered cloning vectors containing variants of IbsC, a 19‐residue toxin from Escherichia coli K‐12. These toxic peptides offer selectivity to minimise the background, labour, and cost associated with conventional molecular cloning. As demonstrated with the cloning of reporter genes, this "detox cloning" system consistently produced over 95 % positive clones. Purification steps between digestion and ligation are not necessary, and the total time between digestion and plating of transformants can be as little as three hours. Thus, these IbsC‐based cloning vectors are as reliable and amenable to high‐throughput cloning as commercially available systems, and have the advantage of being more time‐efficient and cost‐effective.